PROBLEMS AND PROSPECTS OF DIGITAL ECONOMY DEVELOPMENT - G. T. Akhmedova (European Science Publishing, 2023)
The digital economy has become the most dynamic area of technological innovation, service innovation and business innovation in countries around the world. The digital economy is developing rapidly and can bring huge benefits to individuals, organizations and the economy as a whole. However, there are also a number of problems that need to be solved in order to fully realize its potential. One of the main problems is the digital divide, which refers to unequal access of various groups of the population to digital technologies and skills. Another problem is cybersecurity, as the growing dependence on digital technologies makes individuals, organizations and governments vulnerable to cyber-attacks and data leaks. Despite these challenges, the digital economy also provides significant opportunities. One of the main prospects is the potential for innovation and entrepreneurship, as digital technologies create new markets and allow the application of new business models. The digital economy can also increase efficiency and productivity, create new jobs and provide greater access to education, healthcare and other services.
Keywords: digital economy, cybersecurity, new business models, countermeasures, digital technologies, digital payments.